News Accuracy of Firli Bahuri Extortion Case on Tvone and Detik.Com Online Media - Muhammad Akhyaraldo; Sardi Duryatmo; Dini Valdiani (Journal of Social Research, 2025)
This research aims to analyze the differences between two online media, namely TV One and Detik.com, which relate to news about corruption cases committed by Firli Bahuri, who is the former chairman of the Corruption Eradication Commission. This research uses a documentation method with a qualitative approach, namely analyzing the accuracy of news related to the Firli Bahuri Corruption Case in TV One and Detik.com media. Qualitative is research that emphasizes in-depth observation and produces comprehensive studies. This research was carried out through observations by TV One and Detik.com media since November 2023. This research used documentation and observation techniques, meaning that all news related to the Firli Bahuri Corruption Case was carried out by researching TV One and Detik.com media to observe errors in the news. The data collection technique used is news accuracy according to Mencer (2000), which consists of omission, under/over emphasis, misspelling, faulty headline, misquotes, incorrect age, name, date, and location, source attribution errors. The results of this research show that in these six accuracies it was found that errors in news accuracy were very small, this was also proven through interviews from TvOne journalists and Detik.com editors. It can be said that errors in news accuracy from television and online media were very small and did not really affect the news topics presented, TvOne and Detik.com news can still be trusted for their accuracy. In conclusion, analyzing how Firli Bahuri's corruption news in the November-December 2023 and January 2024 editions on TvOne and detik.com media aims to become a source that can be trusted by the wider community to avoid inaccuracies and uncertainties that the public receives.